The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s1678-58782003000100009
|View full text |Cite
|
Sign up to set email alerts
|

Minimum lubrication in Al-Si drilling

Abstract: The high percentage of the refrigeration costs (17%) in the operational production costs, the ecological subjects, the lawlegal demands related to the preservation of the environment and the human health justify the recent researches about the restriction towards the use of abundant cutting fluid in machining processes. However, it is important to point out that the use of a minimal mist lubrication (mixture of air and oil) has been possible in production processes for machining, due to the technological devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Three levels of flow rate and air pressure were used: 20, 40, and 60 ml/h and 1, 2, and 3 bars. The choice of those levels was based on previous studies on MQL drilling of aluminum alloys which applied flow rates in the range of 10 to 100 ml/h and in some cases up to 250 ml/h [8,9,[59][60][61][62][63][64][65][66][67][68].…”
Section: Mql Drilling Trials Setupmentioning
confidence: 99%
“…Three levels of flow rate and air pressure were used: 20, 40, and 60 ml/h and 1, 2, and 3 bars. The choice of those levels was based on previous studies on MQL drilling of aluminum alloys which applied flow rates in the range of 10 to 100 ml/h and in some cases up to 250 ml/h [8,9,[59][60][61][62][63][64][65][66][67][68].…”
Section: Mql Drilling Trials Setupmentioning
confidence: 99%
“…Thus, because the effect of MQL on the process is mainly lubrication and it presents a very small cooling ability to the tool (Braga et al, 2003), it will not cause thermal cracks generation and J. of the Braz. Soc.…”
Section: Results Of the Third Phase -Experiments With Minimum Quantitmentioning
confidence: 99%
“…al. [12] used this technique on drilling Aluminum-Silicon alloy (323) with carbide drills, without coating. The authors concluded that MQL could reduce the temperature on the chip formation zone, maintaining it at levels low enough to avoid tool material deterioration.…”
Section: Introductionmentioning
confidence: 99%